Profile of Bioactive Components of Cocoa (Theobroma cacao L.) By-Products from Ecuador and Evaluation of Their Antioxidant Activity - Wilma Llerena; Iván Samaniego; Christian Vallejo; Adner Arreaga; Billy Zhunio; Zomayra Coronel; James Quiroz; Ignacio Angós; Wilman Carrillo (Foods, 2023)
The aim of the study was to determine the profile of bioactive compounds in cocoa residues (mucilage and bean shells), and to evaluate their antioxidant activity in two cocoa varieties, Nacional X Trinitario type (Fine Aroma) and the variety CCN-51. The extraction of phytonutrients from the residues was carried out selectively. The characterization and quantification of the total polyphenol content (TPC), and the total flavonoid content (TFC) were determined by UV–VIS spectrophotometry. High-performance liquid chromatography (HPLC) was used to determine the phenolic profile and methylxanthines. The antioxidant activity was evaluated by the methods of 2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) cation bleaching (ABTS), ferric-reducing antioxidant power (FRAP) and oxygen radical absorbance capacity (ORAC). The exudate mucilage samples from Nacional X Trinitario-type cocoa presented the highest content of TPC 105.08 mg gallic acid equivalents (GAE)/100 mL, TFC 36.80 mg catechin equivalents (CE)/100 mL, catechin (CAT) 35.44 mg/g, procyanidins (PCB2: 35.10; PCB1: 25.68; PCC1: 16.83 mg/L), epicatechin (EPI) 13.71 mg/L, caffeine (CAF) 0.90% and theobromine (TBR) 2.65%. In the cocoa bean shell, the variety CCN-51 presented a higher content of TPC (42.17 mg GAE/100 g) and TFC (20.57 mg CE/100 g). However, CAT (16.16 mg/g), CAF (0.35%) and TBR (1.28%) were higher in the Nacional X Trinitario cocoa type. The EPI presented no significant differences between the two samples studied (0.83 and 0.84 mg/g). The antioxidant activity values (ABTS, FRAP and ORAC methods) were higher in the samples of CCN-51 than in the Nacional X Trinitario type. The bean shell samples presented antioxidant values of 171.32, 192.22 and 56.87 mg Trolox equivalents (TE)/g, respectively, and the bean shell samples presented antioxidant values of 167.06, 160.06 and 52.53 mg TE/g, respectively. The antioxidant activity (ABTS, FRAP and ORAC) of the residues was correlated with the bioactive compounds of the mucilage and bean shells, showing a strong positive correlation (<0.99) with the procyanidins (B1, B2 and C1), EPI and CAT and a positive/moderate correlation (0.94) with methylxanthines.